IMPROVING THE QUALITY OF TEACHER'S LEARNING THROUGH FRIENDLY CLASS SUPERVISION AT SDN 01 KOTO MARAPAK BARAT 2018/2019 - Husniarni Husniarni (JOURNAL INTERNATIONAL ON GLOBAL EDUCATION, 2022)
Efforts to improve the quality of learning by applying the Active, Innovative, Creative, Effective, and Fun Learning Approach (PAIKEM) through friendlier supervision of SDN 01 Koto Marapak teachers. This research is motivated by teachers who come and go not on time, teachers still use conventional learning, teachers do not make learning tools and the quality of learning is still low. The specific objectives of this PTS activity are to: a) Improve the understanding of teachers at SDN 01 Koto Marapak in developing PAIKEM; b) Improving the skills of teachers at SDN 01 Koto marapak in developing PAIKEM; and c) Improving teacher discipline in carrying out their duties as educators. The benefits of this school action research activity include: a) for teachers, the ability to apply PAIKEM will make it easier to carry out their teaching tasks, because students are more active, while teachers will play more of a facilitator role; b) for students, with the application of the PAIKEM approach, their enthusiasm for learning will be motivated so that they will increase the courage to ask questions, answer questions, take structured actions, find and develop new ideas, so that students' activities and enthusiasm for learning will increase. Thus, through more friendly supervision of SDN 01 Koto Marapak teachers, the following results were obtained: (a) Teacher discipline in carrying out official duties is increasing, (b) Preparation of learning tools has increased from 64.29% in cycle 1 to 83.86% in cycle 2. (c) In the implementation of the learning process increased from 60.91% in cycle 1 to 82.73% in cycle 2. Thus the results of cycle 2 have shown an increase in the quality of learning that is expected to exceed the 80% indicator.